The Fencing Books' collection of the Festetics family - Mátyás Miskolczy (Bern Open Publishing, 2022)
The reproductions of the Fencing Books in the library of the Helikon Palace are made available for research purposes by the owner (the Festetics family), according to a research agreement with the Acta Periodica Duellatorum Association (2022). The desiderata for further research includes codicological description, description of its content and filiation, as well as research on the fighting traditions documented in the corpus (9 books).